Строение частиц химически модифицированного наноалмаза детонационного синтеза - Кулакова, И.И.; Корольков, В.В.; Яковлев, Р.Ю.; Карпухин, А.В.; Лисичкин, Г.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The results of content and structure of chemically modified detonation nanodiamond investigation
with different physical and physical-chemical methods are presented. There aren’t detected
sp2-carbon atoms in nanodiamond. There is found an even distribution of nitrogen admixture in nanodiamond particle volume. It is demonstrated that the crystal structure of ND particles and their
paramagnetic properties are preserved in the process of chemical modification.